The Effectiveness of the Concrete, Pictorial, and Abstract (CPA) Approach in Numeracy Learning for Prospective Students from Central Papua - Enjel Natanael Purba; Wiputra Cendana; Sean Patrick Kang (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Motivated by low numeracy among Papuan children preparing for university, this study examined the effectiveness of the Concrete–Pictorial–Abstract (CPA) approach within the Holistic Academic Readiness Preparation Program (HARPP). A mixed-methods descriptive design combined quantitative measures (an initial diagnostic test and four formative assessments) with qualitative data (classroom observations and semi-structured interviews). Participants were prospective Papuan university students engaged in HARPP interventions that applied CPA consistently and used culturally adapted materials and locally meaningful examples. Quantitative results demonstrated substantial gains: arithmetic operations improved by 75–95% and geometry (Cartesian coordinates) by 78–92.5%. Qualitative findings corroborated these outcomes; students reported increased confidence, reduced anxiety, clearer conceptual understanding, and easier transitions from concrete manipulatives to pictorial representations and symbolic notation. Instructors noted improved student engagement and more effective formative feedback cycles. The study’s novelty lies in embedding the CPA model within Papuan cultural contexts and addressing learners’ unique linguistic and experiential backgrounds while maintaining instructional fidelity. Recommendations include wider implementation of CPA across preparatory programs, curriculum development emphasizing real-world contexts, targeted teacher professional development, and longitudinal research on retention and transfer to higher-level mathematics. Policy implications suggest integrating CPA-informed modules into national readiness programs to reduce equity gaps and improve university preparation outcomes for Papuan students.